STUDENTS’ PERCEPTION ON LECTURER-STUDENT INTERACTION IN ENGLISH AS FOREIGN LANGUAGE (EFL) CLASSROOM - Sri Wahyuni (Getsempena English Education Journal, 2019)
Interaction is communication that happens through more than two people for getting the information, and the interaction is the way for the lecturer in the teaching-learning process in the classroom. Interaction involves all participants in the classroom which are lecturer and students. This study aims to know students’ perception of lecturer-students in EFL classroom interaction at the fourth-semester students of the English department at STKIP Bina Bangsa Getsempena Banda Aceh. This study used a questionnaire to get the data and used a descriptive qualitative design to analyze data. The data were collected by giving a set of a questionnaire (20 questions). The result of this research based on the students’ perception is described the teaching-learning process in the classroom was good enough and the students feel comfortable and surely they like lecturer’s teaching method. The classroom interaction in the EFL classroom is good because the lecturer used not only English but also Indonesia to stimulate the students in understanding what the lecturer explained.